The Regional Human Development and Covid-19 in Aceh - Cut Risya Varlitya; Athala Daffa Khairul; Asyiatul Khafidhah; Salsa Billa Putri Fahri (Economics Development Analysis Journal, 2023)
The world faced a new disease in 2019 called Covid-19, which hit worldwide countries, including Indonesia, and impacted the economic and development obstruction. Human Development Index (HDI) is as one of the development success measurements. This paper analyzes the locally-generated revenue, regional GDP, health spending, and poverty influence on the human development index in the twenty-three districts/cities in Aceh Province using the fixed effect model parameter estimation panel data regression analysis from 2011 to 2020. The results showed that the locally-generated revenue, regional GDP, and poverty increases have caused HDI increases before and during Covid-19. Meanwhile, the government spending on health increased effect only increased the HDI in the years before Covid-19. Health expenditure did not have an impact on HDI during the pandemic because the Covid-19 pandemic spread led to an increased death risk.Therefore, this study recommends the government focuses on providing programs to improve malnutrition and implement clean and healthy living behaviors after the pandemic as to increase the human development quality. Furthermore, the government should update the data on the poor populations and those who are vulnerable to poverty because they have a hard time in rising after the pandemic, so that they are more eligible to receive social assistance